1981
DOI: 10.1111/j.1749-6632.1981.tb33780.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Involvement in Myasthenia Gravis

Abstract: Myasthenia Gravis (MG) has been reported by some authors to be frequently associated with epilepsy, mental diseases, insomnia and endocrine disorders. Other authors have reported electroencephalographic and REMsleep alterations in some MG patients.2 These findings, it has been suggested, are due to a disturbance involving the central nervous system (CNS) acetylcholine receptors; moreover anti-acetylcholine receptor antibodies (anti-AchR) were detected in the CSF of MG patients" and they were supposed to be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…4 Two studies that evaluated brainstem auditory evoked responses reached quite different conclusions. 5,6 Similarly, clinical studies designed to investigate cognitive function in MG have produced conflicting results. Some reports did not find any difference between MG patients and healthy controls, [7][8][9] while others showed cognitive deficits in patients mostly in verbal and visual memory, attention, and learning tasks.…”
mentioning
confidence: 97%
“…4 Two studies that evaluated brainstem auditory evoked responses reached quite different conclusions. 5,6 Similarly, clinical studies designed to investigate cognitive function in MG have produced conflicting results. Some reports did not find any difference between MG patients and healthy controls, [7][8][9] while others showed cognitive deficits in patients mostly in verbal and visual memory, attention, and learning tasks.…”
mentioning
confidence: 97%
“…Ferguson et al 32 found in 18 amyotrophic lateral sclerosis patients compared with 10 healthy controls reduced total sleep time, a larger proportion of stage 1 NREM sleep, increased arousals per hour, and more frequent sleep stage changes per hour. Bergonzi et al 13 found in 17 subjects with myasthenia gravis compared to normal subjects matched for age and gender significantly less REM and more NREM sleep, a shorter average REMperiod length, a shortened REM-stage latency, and an increase in the number of stage changes. Papazian 17 found in 10 stable myasthenia gravis subjects compared with 5 controls significant reductions in total duration, percentage and number of REM periods, and a greater percentage of NREM (especially stages 3 and 4) sleep; in addition, the number and durations of REMs withing each individual REM period were reduced.…”
Section: Altered Sleep Architecture In Subjects With Muscle Weaknessmentioning
confidence: 97%
“…[10][11][12] In support of the notion of pharyngeal muscle dysfunction leading to sleep apnea and alterations in sleep architecture are a number of studies examining sleep and breathing during sleep in (generally a small number of) subjects with disorders of skeletal muscles or the neuromuscular junction-myotonic dystrophy, Duchenne muscular dystrophy, and myasthenia gravis. [13][14][15][16][17][18] These studies have described a high prevalence of sleep apnea (e.g., 11 of 20 subjects with myasthenia gravis studied at time when they were clinically stable had a respiratory disturbance index of greater than 5), 18 worsening of nighttime hypoxemia over time (e.g., 9 of 10 patients with muscular dystrophy who were hypoxemic at their initial evaluation had worsened hypoxemia at a follow-up study), 16 (e.g., reduced rapid eye movement sleep was found in two separate studies of 17 and 10 patients with myasthenia gravis). 13,17 Furthermore, nighttime oxygen desaturation has been associated with poor long-term survival in subjects with muscular dystrophy: subjects with desaturation >4% had a median survival of 30 months versus 90 months in those with lesser degrees of desaturation.…”
Section: Review Articlementioning
confidence: 97%
See 2 more Smart Citations